The Study of Rice Potential Production on Namu Sira-Sira Irrigation Fields in Sei Bingai District Langkat Regency - Tri Ayu Purnamasari; Sumono Sumono; Lukman Adlin Harahap (Universitas Sumatera Utara, 2014)
Langkat as one of rice centra region in North Sumatera need to be inspected on wet rice fields condition to hold out and increase production. The purpose of this research was to study the rice potential production on Namu Sira-Sira irrigation fields in Sei Bingai district Langkat regency in achieving the maximum level of rice production based on sun radiation level, time to grow rice, and rice variety. This research also studied the ratio between irrigation field and crops field, the ratio between technical irrigation and pre technical and conventional irrigation and realibility of existing irrigation networks. In the year of 2009-2013, the results indicated that the irrigation network realibility was good enough. The average ratio between irrigation field and crops field was 2,2, the average of ratio between technical irrigation and pre technical and conventional irrigation was 5,82 and the rice production target was 70,68%. Keyword : irrigation network, potential production, production target, rice